Abraham model correlations for describing solute transfer into anisole based on measured activity coefficients and molar solubilities. (4th May 2022) - Kim, Kelly; Shanmugam, Neel; Xu, Angelina; Varadharajan, Advika; Cai, Sophia K.; Huang, Evonne; Acree, William E.
ABSTRACT: Mole fraction solubilities are reported for anthracene, pyrene, salicylamide, benzoin, benzil, thioxanthen-9-one, 1-chloroanthraquinone, and 4-methyl-3-nitrobenzoic acid dissolved in neat anisole at 298.15 K based on spectrophotometric measurements. Results of the experimental measurements, combined with published infinite dilution activity coefficient and solubility data gathered from the published chemical literature, are used to derive Abraham model expressions for describing solute transfer into anisole from both water and the gas phase. The derived mathematical equations describe the observed solute transfer coefficients to within the overall standard deviations of 0.14 log units (or less).